Sinter‐ and Water‐Resistant Pt Enabled by High Entropy of Porous Oxide Nanofibers - Yunpeng Wang; Mingyu Tang; Zhuxin Lyu; Wanlin Fu; Han Yan; Shiming Zhou; Yueming Sun; Yunqian Dai (Advanced Science, 2025)
Abstract Supported ultrafine noble metal species, especially for Pt, suffer from inevitable sintering at temperatures as low as 80 °C, severely limiting their stability and thus their practical applications. In this work, a strategy is demonstrated using the high‐entropy effect to prevent sub‐2.6 nm Pt nanoparticles from sintering. Due to the higher mixing entropy and thus lower Gibbs free energy of porous high‐entropy oxide (HEO) nanofibers in the catalytic system, the supported Pt remained thermally stable up to 1000 °C, as verified by in situ HAADF−STEM observation. Even after being hydrothermally aged with 10 vol% vapor at 850 °C, this catalytic system maintained the Pt size of 2.9 nm, demonstrating remarkable sinter‐resistance and water tolerance. Particularly, after aging at 850 °C, the Pt/HEO catalytic system maintained its full CO conversion for 338 h without any decline. These results highlight the positive effect of increasing configurational entropy on the thermal stability of the entire catalytic system, providing a reliable solution for catalytic conversions involving high temperatures.